1991
DOI: 10.1097/00006842-199109000-00004
|View full text |Cite
|
Sign up to set email alerts
|

Biobehavioral basis of coronary-prone behavior in middle-age men. Part II: Serum cholesterol, the Type A behavior pattern, and hostility as interactive modulators of physiological reactivity.

Abstract: Prior research suggests that the Type A behavior pattern, Cook and Medley Hostility (Ho) scores, and Total Serum Cholesterol (TSC) are positively associated with physiological changes to behavioral stressors. The objective of the present study was to determine whether TSC interacts with the Type A behavior pattern and hostility to affect cardiovascular and neurohormonal responses to a mental arithmetic task (MATH). For Type A individuals, elevated TSC was associated with larger catecholamine and cortisol respo… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

1
10
0
1

Year Published

1992
1992
2010
2010

Publication Types

Select...
7
2
1

Relationship

0
10

Authors

Journals

citations
Cited by 66 publications
(12 citation statements)
references
References 26 publications
1
10
0
1
Order By: Relevance
“…Subsequent research has strongly suggested that sympathetic nervous system (SNS)-mediated hyperresponsivity to behavioral stressors is associated with elevations in serum lipids. One study by Suarez et al (1991) showed greater catecholaminergic (i.e., epinephrine and norepinephrine) responses among men exhibiting Type A hostility as opposed to Type B (low-hostility) responders. For both human and animal populations SNS excitation, in the form of an increase in circulating catecholamine, has been implicated in the elevation of cholesterol levels (Jorgensen et aL, 1988).…”
Section: Discussionmentioning
confidence: 99%
“…Subsequent research has strongly suggested that sympathetic nervous system (SNS)-mediated hyperresponsivity to behavioral stressors is associated with elevations in serum lipids. One study by Suarez et al (1991) showed greater catecholaminergic (i.e., epinephrine and norepinephrine) responses among men exhibiting Type A hostility as opposed to Type B (low-hostility) responders. For both human and animal populations SNS excitation, in the form of an increase in circulating catecholamine, has been implicated in the elevation of cholesterol levels (Jorgensen et aL, 1988).…”
Section: Discussionmentioning
confidence: 99%
“…The slower stress recovery of blood type O people would decrease the amount of TxPA available to protect them from the injurious effects of VLDL after stress or emotional upset relative to blood type A individuals. Several CAD risk factors such as total serum cholesterol and blood viscosity have also been correlated with acute stress response and emotional traits/behavior patterns (7,24,25). It is unknown how TxPA correlates with these and many other CAD risk factors.…”
Section: Discussionmentioning
confidence: 99%
“…Anger states can also elevate catecholamine levels transiently [51], but it is unclear whether such increases are sustained over time or occur more frequently in persons with high trait anger scores, high anger expression, or high anger inhibition. It is also unclear whether increases in catecholamines due to anger states can actually lead to hypertension.…”
Section: Biological Plausibility Issuesmentioning
confidence: 99%